Simulating the spatio-temporal dynamics of soil erosion, deposition, and yield using a coupled sediment dynamics and 3D distributed hydrologic model. (September 2016) - Zi, Tan; Kumar, Mukesh; Kiely, Gerard; Lewis, Ciaran; Albertson, John
Abstract: Since soil erosion is driven by overland flow, it is fair to expect heterogeneity in erosion and deposition in both space and time. In this study, we develop and evaluate an open-source, spatially-explicit, sediment erosion, deposition and transport module for the distributed hydrological model, GEOtop. The model was applied in Dripsey catchment in Ireland, where it captured the total discharge volume and suspended sediment yield ( SSY ) with a relative bias of −1.2% and −22.4%, respectively. Simulation results suggest that daily SSY per unit rainfall amount was larger when the top soil was near saturation. Simulated erosion and deposition areas, which varied markedly between events, were also found to be directly influenced by spatial patterns of soil saturation. The distinct influence of soil saturation on erosion, deposition and SSY underscores the role of coupled surface-subsurface hydrologic interactions and a need to represent them in models for capturing fine resolution sediment dynamics. Highlights: An open-source, spatially-explicit, sediment dynamics model was developed. The model was validated at both plot and catchment scales. Error in runoff estimates influences the accuracy of simulated suspended sediment yield. Daily precipitation intensity did not fully explain the variance in daily SSY. Simulated spatial patterns of erosion/deposition were influenced by surface soil saturation.